Dispositivo fotorrefrativo revestido de material compósito para medição simultânea de vibração e temperatura em núcleo de transformadores - Kuhn, Gustavo Gomes (2020)
This work presents studies on the identification of mechanical vibrations and temperature originating in the iron core of a three-phase dry transformer. Different frequency components can generate losses and damages through mechanical vibrations. The loss of insulation causes major failures such as short circuits, which end up generating losses to energy concessionary and mainly to final consumers. Unlike commercial electrical sensors, which are attached to the transformer’s external housing, this study proposes the application of Bragg gratings in optical fiber (FBG) as sensor elements applied directly to the core, simultaneously monitoring dynamic vibration and temperature. Also compared to traditional electrical sensors (strain gages), FBGs sensors do not suffer electromagnetic interference, and can be applied internally to the transformer without optical signal attenuation. In addition, it monitors vibration directly at the main causative source, which is the iron core. As the sensor is exposed to a hostile environment, a carbon fiber reinforced composite device is designed to protect the optical fiber. The optical sensors were coated by the composite, which also has the function of improving the sensitivity to dynamic deformation of the sensor. The part geometry has a spring shape that guarantees this increase in sensitivity by approximately 12.3 % for the 120 Hz mechanical fundamental frequency component. For the measurement of temperature and vibration, two multiplexed sensors with different wavelengths were used. The temperature compensation of the strain sensor was also performed. Electrical tests on a 3 kVA three-phase dry transformer were carried out with different types of electrical loads. The Frequency Response Function (FRF) was used to present the dynamic deformation results and compare the FRFs of sensors glued freely to the core with the embedded sensors. The quick coupling device, in the experimental tests, obtained an average sensitivity increase ratio of 32 % in relation to the non-encapsulated sensor. Thus, direct application to the iron core of three-phase dry transformers was shown to be feasible.